Przykładowy plan badań głosu i mowy dzieci z zespołem Downa z zastosowaniem nowoczesnych narzędzi diagnostycznych - Zielińska, Jolanta (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article presents an exemplary plan of voice and speech testing in children with Down syndrome using modern diagnostic tools. As a theoretical basis of planned research was presented myoelastic-aerodynamic theory of phonation. Then, two research areas were presented. The first is application in assessment voice and speech of modern computer technology. A diagnostic and exploratory goal of this test is to assess the voice and speech of children with Down syndrome using the laryngography technique. The second research area covers the assessment made by the parents or guardians of the voice status of children in based on the Polish adaptation of the Pediatric Voice Disability Assessment Questionnaire Voice Handicap Index (pVHI) (Krasnodębska et al., 2019). A practical and implementation goal of presented research is to formulate indications for an objective and reliable diagnosis combining traditional diagnostic methods with modern measurement techniques and developing indications for an effective therapy process.